Antibacterial actifity of kecombrang (Etlingera elatior) leaf ethanol extract to against Klebsiella pneumoniae - Eka Puspitasari; Chalies Diah Pratiwi; Dede Rival Novian; Dora Dayu Rahma Turista (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
Infectious diseases caused by bacteria in generals can be cured using antibacterial. The use of antibacterials tends to cause local hypersensitivity either on the skin or mucous membranes so that their use is starting to be reduced. Therefore, the development of natural antibacterials made from plants to reduce resistance is very necessary. kecombrang (Etlingera elatior) is one of the plants that has been shown to have activity in inhibiting bacterial growth. This research is an experimental study that aims to determine the effectiveness of the ethanol extract of the leaves of kecombrang in inhibiting the growth of Klebsiella pneumoniae bacteria in vitro. The method used is the well method with a completely randomized design. The sample came from the Klebsiella pneumoniae bacteria culture. Kecombrang leaf ethanol extract was made in concentrations of 20%, 40%, 60%, 80% and 100%. The extract was tested on Klebsiella pneumoniae bacteria and observed for the formation of inhibition zones. Inhibition the results of the zone measuremens were then analyzed descriptively. The results showed kecombrang leaf ethanol extract 20%, 40%, 60%, 80%, and 100% produce inhibition zone diameter 1.9 mm; 2.6 mm; 7.7 mm; 12.1 mm; and 14.7 mm, 0.4 mm for the negative control and positive control 22.0 mm. Concentration 100% has better antibacterial ability due to higher compound content. The test results show the class of secondary metabolites kecombrang leaf ethanol extract contains flavonoids, tannin, and saponin. The conclusion of this study that the ethanol extract of kecombrang leaves has potential to inhibit the growth of Klebsiella pneumoniae bacteria.